Teaching the Art of Mathematical Modelling - MAURYA, R.P. (SCHOOL SCIENCE, 2007)
We are aware of the solution of word problems in arithmetic, algebra, trigonometry, calculus probability and linear programming. Sometimes students solve the problems without conceiving the physical picture of the situation presented by a given problem. Situational problems often need physical insight, that is, understanding of physical laws and some symbols to comprehend the mathematical results obtained with observed/practical values. We do not perform any practical activity, we do not approach the situation at all or we do not take any sample of blood to know human physiology, still our mathematics reveals the actual situation. So, to solve many problems pertaining to various fields including scientific research, there is an urgent need of developing the art of mathematical modelling right from the school stage.